The interaction of the vanadyl (IV) cation with chondroitin sulfate A - Etcheverry, Susana Beatriz (1994)
The interaction of VO2+ with the muchopolysaccharide chondroitin sulfate A (CSA) has been investigated by electron absorption spectroscopy and infrared measurements in aqueous solutions at different pH-values and ligand to metal ratios up to 6:1. The generation of a VO(CSA)2 species could be demonstrated. Coordination of the oxocation through the carboxylate group and the glycosidic oxygen of thed-glucuronate moieties is suggested. Infrared spectra of some poorly characterized solid VO/CSA complexes point to the same bonding characteristics. Preliminary results obtained at higher ligand to metal ratios suggest a different coordination behavior.